2019
DOI: 10.3389/fevo.2019.00466
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down and Bottom-Up Effects Deployed by a Nurse Shrub Allow Facilitating an Endemic Mediterranean Orchid

Abstract: Aims: Facilitation among plant species occurs when the presence of one species, the so-called nurse, alters the environment in a way that enhances the growth, survival or reproduction of a second species. This positive association could be specie-specific and can have direct top-down (canopy) or bottom-up (soil) effects as well as indirect effects like higher tolerance against herbivory. The main objective of our study was to determine the positive interaction between the endemic Chilean orchid Bipinnula fimbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Water availability was not directly measured, but is relatively safe to assume that a lower temperature and light will induce a lower water vapor deficit and evaporation from the soil, thus resulting in a higher water availability within the canopy of shrubs. Moreover, a related study in one of the three sites (PCU) found that water availability was higher inside shrubs compared to open areas as expected (Baldelomar et al 2019). The amelioration of biotic and abiotic stress inside the canopy of a nurse plant has been widely documented (Domingo et al 1999;Pugnaire et al 2004;Cavieres et al 2005;Gozález-Teuber and Gianoli 2008;Tracol et al 2011;Molina-Montenegro et al 2016).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Water availability was not directly measured, but is relatively safe to assume that a lower temperature and light will induce a lower water vapor deficit and evaporation from the soil, thus resulting in a higher water availability within the canopy of shrubs. Moreover, a related study in one of the three sites (PCU) found that water availability was higher inside shrubs compared to open areas as expected (Baldelomar et al 2019). The amelioration of biotic and abiotic stress inside the canopy of a nurse plant has been widely documented (Domingo et al 1999;Pugnaire et al 2004;Cavieres et al 2005;Gozález-Teuber and Gianoli 2008;Tracol et al 2011;Molina-Montenegro et al 2016).…”
Section: Discussionmentioning
confidence: 53%
“…In Chile, adult plants of Chloraea and Gavilea also associate with mycorrhizal fungi with Rhizoctonia-like traits (Pereira et al 2014;Atala et al 2015;Herrera et al 2017). However, to the date, their ecology has been less studied (but see Cuartas-Domínguez and Medel 2010;Atala et al 2017;Baldelomar et al 2019). Understanding their ecological interactions could be essential for their conservation in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate actions are require to avoid the extinction of C. disoides in the relatively short term, threatened by human actions and climate change (Atala et al 2017). Thus, further studies are required to establish the most efficient method for obtaining adult individuals, and, eventually, make possible the re-introduction of plants in the field, where with the aid of native shrubs it may be possible to ensure survival in the long term (Baldelomar et al 2019, Atala et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the plant diversity is a major challenge in plant community ecology (Gonzalez & Ghermandi, 2019). Although classical studies on this issue have focused on the negative plant–plant interactions, more recent studies have considered the importance of the positive interactions, such as the nurse effect of larger plants on smaller ones (e.g., Baldelomar, Atala, & Molina Montenegro, 2019). At the landscape level, shrubs could reduce plant diversity (Ratajczak, Nippert, & Collins, 2012), while at the patch level, they are known as nurse plants due to their positive effects on sub‐canopy and increasing plant diversity (see Gómez‐Aparicio et al, 2004).…”
Section: Introductionmentioning
confidence: 99%